The Effect of Probiotics on Hematology Profille of Domestic Chicken (Gallus domestiicus) - Widiandini, Dara Adisti; Karim, Rizqi Mildia Nur; Susilowati, Aprilia; Putri, Camila Azzahra Hadi; Gianina, Gianina; Hasyyati, Hening; Siregar, Yohana Merylin; Mufliha, Salsabila Hasna; Yuliani, Gandul Atik (Universitas Airlangga, 2022)
Domestic chickens are one of the most important commodities in fulfilling animal protein needs in Indonesia. Despite its advantages in environmental adaptability and ease of maintenance, local chickens also have the disadvantage of low productivity. The health of native chickens is a key factor affecting their productivity, and quality feed is important in supporting this health. To improve efficiency and productivity, improved feed is the main focus, but the use of antibiotics as growth promoters has been banned due to their residues in the body of the livestock. Alternatively, the use of probiotics in feed is a promising solution due to their benefits in improving gut microflora balance and overall health. Blood profile was used as a parameter to evaluate the health of livestock after feeding probiotics. This study aims to investigate the effect of probiotics on the hematological profile of kampung chickens including the number of erythrocytes, the number of leukocytes, hemoglobin levels, and hematocrit values. Experimental approach by applying four different treatments. The four treatments used were K0 (Use of basal feed), K1 (Use of basal feed supplemented with probiotics in liquid form at a concentration of 0.1 v/w.), K2: (Use of basal feed supplemented with probiotics in liquid form at a concentration of 0.3 v/w). K3 (Use of basal feed supplemented with probiotics in liquid form at a concentration of 0.5 v/w). At the next stage, observations were made on hematological profile parameters to evaluate the results of each treatment given. Based on the results of the research that has been done, it is found that the provision of probiotics affects the hematological profile of domestic chickens, the addition of probiotics can increase the number of erythrocytes, the number of leukocytes, hemoglobin levels, and hematocrit values. With an average erythrocyte count of 2.44 x 106/mm3, leukocyte count of 23.75 103/mm3, hemoglobin level of 11.25 g/dl, and hematocrit value of 11.25%.